Design and implementation of CMOS rail-to-rail operational amplifiers - Lorenzo, Michael Angelo G. (2006)
Operational amplifiers have become fundamental components in various applications in the electronics field. The industry's trend towards low-power and lower-supply voltages demands maximizing the op-amps' signal range. Rail-to-rail op-amps make the most out of these small signals by including the entire voltage supply range in its region of operation. The goal of this project is to design and implement an operational amplifier with rail-to-rail input and output capability. ths study characterizes rail-to-rail input and output stages and the dependence of the op-amp's operation on different design parameters such as transistor sizes and biasing. A standard design methodology for rail-to-rail op amps is formulated from the characterization. The report shows the effects of the rail-to-rail stages on the op-amp's input common-mode range and output voltage swing range and other parameters such as gain, bandwidth, offset voltages and common mode rejection ratio. The project is able to implement rail-to-rail op-amps with specifications comparable with commercially available circuits. The project is a pioneer implementation of rail-to-rail op-amps in the laboratory and it fulfilled its objective of building a starting ground for possible future studies in the area of rail-to-rail op-amps. The achievements of the study recommend the utilization of the rail-to-rail operational amplifiers in future op-amp applications and research projects.